PENGARUH MOTIVASI DAN KOMITMEN ORGANISASIONAL PADA KINERJA GURU DIMEDIASI OLEH KEPUASAN KERJA - Lie Lilianna; Suhana Suhana; Romadi Romadi (AMIK Jakarta Teknologi Cipta Semarang, 2017)
Education has a povital role for a progress of a country. In the education process intended, teacher position holds a key role. To guarantee good quality of education, to increase the teacher performance is very important. Teachers in Elementary School in UPT Dindikbud Doro Pekalongan Regency undergoes performance decreasing in the last three years successively. The indication could be seen from the result of national exam, from 2012-2014 undergoing declining successively. Theoretically, there are many factors being predicted to have effect on performance. From the previous studies, it is known that performance could be affected by motivation, organizational commitment and job satisfaction. The current research discusses variables linked with elementary school teacher performance in UPT Dindikbud Doro Pekalongan Regency. The population is 2019 teachers and 142 teachers are the samples. Analysis technique used in the research is regression and path analysis. Of analysis conducted, it is derived research findings, as follows: motivation has a positive effect on job satisfaction, organizational commitment has a positive effect on job satisfaction, motivation does not affect teacher performance, organizational commitment affects teacher performance, job satisfaction mediates the effect of motivation to teacher performance and organizational commitment to teacher performance. The research has a theoritical and managerial implication. From theoritical point of view, the results contributes to the model of relationship among variables. Meanwhile, from managerial point of view, the results could be input for the decision makers to increase teacher performance. Keywords: teacher performance, job satisfaction, motivation and organizational commitment